Remolding and resistance among writers of the Chinese prison camp: disciplined and published - Williams, Philip F.; Wu, Yenna (Routledge studies in Asia's transformations, 2006)
The repercussions of thought remolding and forced labor on Chinese writers: Introduction -- Zhang Xianliang as author and hero: A study of his Record of My Emotional Life -- Traumatic "remolding" and its ethical implications in three of Zhang Xianliang's novels -- Labor camp fiction as conversion literature: Zhang Xianliang and Oaka Shohei -- Resisting the regime of remolding -- Expressing the "inexpressible": Pain and suffering in Wumingshi's Hongsha [Red Sharks] -- Profit and loss in China's contemporary prison system